Anti-NMDA receptor encephalitis unmasking Sjögren’s disease: a case report and literature review - Dimitrov, Gabriel; Deneva, Vanya; Mantarova-Valkova, Stefka (Frontiers in Immunology, 2026)
Anti-N-methyl-D-aspartate (NMDA) receptor encephalitis is an autoimmune central nervous system (CNS) disorder mediated by antibodies against the GluN1 subunit of the NMDA receptor. Sjögren’s disease (SjD) is a systemic autoimmune disorder that involves exocrine glands as a primary target. However, CNS manifestations, including the coexistence of other CNS diseases, may also occur. While antibodies against the NMDA receptor, targeting the GluN2 subunits, have been associated with SjD and neurological symptoms, the presence of GluN1 antibodies is rarely described, and the co-occurrence of these two disorders has been scarcely reported. Here, we present a case in which anti-NMDA receptor encephalitis and SjD were identified concurrently during the initial workup. The patient experienced three attacks over 13 months, each effectively treated with immunotherapy. No symptoms were reported during the final phone call (month 18). This case report illustrates the ‘unmasking’ of occult systemic autoimmunity by a non-specific neurological syndrome. A comprehensive diagnostic approach is essential to uncover polyautoimmunity and avoid premature diagnostic closure. Further studies may be required to determine whether the association between SjD and NMDA receptor autoimmunity extends beyond the GluN2 subunits to include the pathogenic GluN1 subunit antibodies.